The Effect of Ozone Therapy on the Treatment of Diabetic Foot Ulcers: a review (Ozone Therapy Global Journal, 2020)
Diabetes Mellitus is one of the most common metabolic diseases and one of the main causes of death in modern society. The prolonged increase of glucose in the blood and urine causes serious complications in various organs in the body. One of its main complications is the diabetic foot ulcer and it is responsible for numerous hospitalisations, amputations, being associated with significant morbidity and mortality, in addition to its immense social, psychological and financial impact. Taking into account the benefits of ozone and its multiple applications; its application in the treatment of diabetic foot ulcers is considered to be adequate. The use of ozone treatment is encouraged for its circulation stimulating properties which favour tissue oxygenation in addition to its analgesic, anti-inflammatory and germicidal effects. The aim of this work is to get acquainted with one of the main complications of diabetes and its response to ozone treatment- topical application. The methodology used was the literature review carried out in the Spanish Journal of Ozone Therapy. The descriptors used were: ozone, ozonized water, ozonized oil, diabetic foot and ozone bag. The application of ozone in diabetic foot ulcers is assumed to be an effective and safe therapy with positive results in improving the quality of life of those living with the pathology, by avoiding the occurrence of complications such as amputations. Therefore, we can affirm that clinical evidence supports the use of ozone in the treatment of diabetic foot ulcers..